DEVELOPMENT OF SOLAR THERMOELECTRIC GENERATOR - Maslamani, Taleb M.; Omer, Abdu Idris; M. A., Majid (European Scientific Journal, ESJ, 2014)
Concentrating solar power (CSP) is a unique renewable energy technology. CSP systems have the ability to provide electricity, refrigeration and water purification in one unit. This technology will be extremely helpful in improving the quality of life for many people around the world who lack the energy needed to live a healthy life. A thermoelectric generator is a solid-state device that converts a heat flux into electrical power via the Seebeck effect. When a thermoelectric generator is inserted between a solar-absorbing surface and a heat sink, a solar thermoelectric generator is created which converts sunlight into electrical power. This project describes the design and optimization of solar thermoelectric generators, with a focus on systems with high optical concentration which utilize multiple material systems to maximize efficiency over a large temperature difference. a single-stage generators are considered, over an optical concentration range of 0.1 to 1000X. It is shown that for highconcentration solar thermoelectric generators, conversion efficiencies of 13% are possible with current thermoelectric materials and selective surfaces. The assembled system as the concentrator thermo electric generator CTEG is able to produce electric power of up to 5.5W under the temperature difference of 35°C. The experimental results showed a considerable agreement with the mathematical model as well as its potential application